Robot-Assisted Total Knee Arthroplasty: A Literature Review of Accuracy, Complications, Cost-Effectiveness, and Clinical Outcomes - Deria Zahra Fatihah; Juniarto Jaya Pangestu; Norman Zainal (Green Publisher Indonesia, 2026)
Background: Conventional Total Knee Arthroplasty (C-TKA) still faces challenges with high patient dissatisfaction rates, often linked to malalignment. Robot-Assisted TKA (RA-TKA) was developed to improve surgical precision. Despite its rapid adoption, there are conflicting findings regarding its advantages over C-TKA, along with concerns about cost and the learning curve. Objective: This literature review aims to comprehensively analyze and compare RA-TKA with C-TKA, focusing on four domains: (1) surgical accuracy and alignment; (2) complication rates; (3) cost-effectiveness; and (4) clinical outcomes. Findings: The review found that RA-TKA consistently demonstrates superior accuracy in restoring the mechanical axis (HKA) and coronal alignment, significantly reducing the number of outliers. RA-TKA also facilitates dynamic soft tissue balancing. However, findings regarding sagittal plane accuracy (e.g., tibial slope) remain contradictory across different robotic platforms. RA-TKA consistently requires longer operative times, especially during the learning curve, and introduces new technical risks such as pin failure and pin-site fractures. While the risk of major complications (e.g., PJI) is comparable, RA-TKA shows a lower risk of postoperative stiffness (arthrofibrosis). Evidence on mid-term revision rates remains inconclusive. Cost-effectiveness analysis shows that the high initial capital cost necessitates a very high procedural volume to achieve cost efficiency. Conclusion: RA-TKA offers clear advantages in coronal alignment precision but is offset by high costs, longer operative times, and specific robotic complications.